Classical music and postmodern knowledge - Kramer, Lawrence, 1946- (University of California Press, 1995)
A leading cultural theorist and musicologist opens up new possibilities for understanding mainstream Western art music--the ""classical"" music composed between the eighteenth and early twentieth centuries that is, for many, losing both its prestige and its appeal. When this music is regarded esoterically, removed from real-world interests, it increasingly sounds more evasive than transcendent. Now Lawrence Kramer shows how classical music can take on new mean.